PENGARUH KONSENTRASI MALTODEKSTRIN DAN SARI JERUK NIPIS TERHADAP TINGKAT KESUKAAN ORGANOLEPTIK MINUMAN INSTAN MENTIMUN (Cucumis sativus L.) - Mei Dita Fitrotus Zakiyah; Rahmah Utami Budiandari; Rima Azara; Ida Agustini Saidi (Fakultas Pertanian Universitas Riau, 2024)
Cucumber is a fresh fruit that is commonly consumed and is rich in vitamins and minerals. In addition, cucumber production is also abundant. Lime juice has a sour taste and is high in vitamin C. Both agricultural commodities have a short shelf life so that further processing is needed, namely instant powdered drinks using the foam mat drying method. This study aims to determine the organoleptic characteristics of instant cucumber powdered drinks. The study used Randomized Complete Block Design (RCBD) experiment, the first factor was the concentration of maltodextrin (15, 20, and 25%) and the second factor was the concentration of lime (5, 15, and 25%). The organoleptic test used a hedonic test, and the data were analyzed using the Friedman method. The organoleptic results in the treatment of 25% maltodextrin and 25% lime showed organoleptic color 3.47 (neutral), aroma 3.37 (neutral), texture 3.57 (like) and taste 3.93 (like).